Supply-driven translation in a small nation context: Slovene literature in English 1991-2016 - Hellewell, Olivia (2019)
This thesis is an analysis of Slovene literature translated into English during the first twenty-five years of Slovene independence following the country’s secession from the Socialist Federal Republic of Yugoslavia (SFRY) in 1991. It takes the case study of this so-called small nation to illustrate how, in the context of this culture’s relatively low visibility in the global language of English and against the backdrop of a varied set of political circumstances over the past century, Slovene literature has been translated largely at the hands of agents based in the source culture (SC) itself. It builds on a small body of Translation Studies (TS) research concerned with ‘supply-driven’ translation, offering an in-depth examination of how this type of literary translation activity, initiated in the SC, takes place in this particular context. The thesis argues that in the Slovene case, there are three main strands of supply-driven translation activity that lead to the existence of Slovene literature in English, and these are academic, institutional and individual types of supply. The production of literature is viewed as a system, drawing on Even-Zohar’s polysystems hypothesis, but the thesis looks beyond a purely systems-based perspective, arguing that the ideas of Pierre Bourdieu – the concepts of cultural capital and field in particular – are necessary to understand the role of agents and institutions in the production of literary translations. Finally, the thesis considers the impact of these supply-driven translation activities upon the body of work that is produced. In the US and UK target cultures (TCs), where translated literature constitutes around 3% of all published literature, translated novels are presented and accessed by readers in relation to their country of origin. This thesis therefore examines what Slovene literature is to an anglophone audience – what it consists of in content, and how it’s presented – and how Slovenia is represented within it, based on an analysis of the novels’ presentation through paratexts. To complement the broader analysis of the corpus, this thesis incorporates a close literary analysis of three novels, in which the representation of landscapes, themes and motifs are considered, questioning how these devices construct ‘Slovenia’ for an anglophone audience. As a result, the thesis contributes data on contemporary translation processes from a perspective that showcases the agency of authors, translators and other cultural actors in constructing a body of work in English translation driven not by a demand in the TC, but by a variety of motivations shaped by the SC literary field.